Host quality of different aphid species for rearing Diaeretiella rapae (McIntosh) (Hymenoptera: Braconidae) - Silva, RJ [UNESP]; Cividanes, Francisco Jorge [UNESP]; Pedroso, EC [UNESP]; Sala, SRD [UNESP] (Sociedade Entomológica do Brasil, 2011)
This study aimed to evaluate the quality of the aphid Myzus persicae (Sulzer), Lipaphis erysimi (Kaltenbach) and Brevicoryne brassicae (L.) as hosts for the parasitoid Diaeretiella rapae (McIntosh). Parasitization by D. rapae was higher on M. persicae than on L. erysimi and B. brassicae. The time of development of D. rapae from egg to mummy or egg to adult male or female were shorter on M. persicae than on L. erysimi and B. brassicae. Moreover, D. rapae showed no significant differences in the emergence rate, sex ratio and longevity when reared on the three aphid species. Myzus persicae was the largest aphid host, with B. brassicae and L. erysimi being of intermediate and of small size, respectively. Diaeretiella rapae reared on M. persicae was larger than when reared on L. erysimi and B. brassicae, and females of D. rapae were significantly larger than males on M. persicae, but males of D. rapae were larger than females when reared on L. erysimi. No difference in size was detected between males and females in parasitoids reared on B. brassicae. Among the aphid species studied, M. persicae was found to be the most suitable to D. rapae.
Keywords: Brassicaceae; glicosinolate; Myzus persicae; Lipaphis erysimi; Brevicoryne brassicae